Agitporn Colombia(a fanzine): : "From porn to bioterrorism" (DAPesquisa, 2020)
AGITPORN COLOMBIA: "From porn to bioterrorism" (2018) is a zine-script for daily performances created in and for the Colombian context, however it can also be translated into several other Latin American contexts. It is the result of the doctoral research project ABC of the struggle of native peoples from Brazil: performances, pedagogies, propaganda and political (images) for social decolonization that I have been developing at PPGT-UDESC under the guidance of Profa. Dr. Fátima Costa de Lima and the artistic residence Abejas TAPIOCA with the collective Corporación TAPIOCA and contemplated by IBERESCENA, held between July and September 2018 with indigenous people "desplazadas" from their territories by guerrilla and / or drug trafficking. This publication is a Portuguese translation from Spanish with a short introduction and an exchange of electronic messages organized for DAPesquisa journal.
Keywords: Theater programs; Indians of South America - Colombia-Themes, motives; Performance art